Composition of Household Income and Child Nutrition Outcomes Evidence from Uganda. (September 2018) - Kirk, Angeli; Kilic, Talip; Carletto, Calogero
Highlights: This study takes advantage of income and height measurements from three years of the Uganda National Panel Survey. No correlation of short-term changes in income and height measures overall but small positive correlation for younger kids. Compared to wages, only share of income from nonfarm self-employment correlates positively with HAZ in the sector analysis. In agriculture, income shares from (i) consumption of own crops and (ii) low-protein crop production show negative effects. Overall, any effects are small, in a context where many households maintain a diversified portfolio. Summary: This study targets the empirical space between cross-country analyses exploring links between income and nutrition without insights on micro-level determinants, and relevant microeconomic studies hindered by small sample size and/or incomplete data. We use the rural samples of the three waves of the Uganda National Panel Survey, and estimate panel regressions of child height-for-age z -scores (HAZ) controlling for time-invariant child-level heterogeneity. On the whole, we find no impact of short-term changes in total gross income on HAZ but document small positive correlations for younger children. Sector-differentiated analyses indicate that compared to wage earnings, only share of income from non-farm self-employment correlates positively with HAZ. Within agriculture, shares of income from consumption of own crop production and from low-protein crop production underlie the negative effect of share of income from crop production. While we cannot claim causal relationships, our findings suggest the possibility of "stickiness" of crop production to own consumption.